Handbook on multi-level governance - Enderlein, Henrik; Walti, Sonja; Zurn, Michael (Cheltenham, [England] Edward Elgar, 2010)
Scholarship of multi-level governance has developed into one of the most innovative themes of research in political science and public policy. This accessible Handbook presents a thorough review of the wide-ranging literature, encompassing various theoretical and conceptual approaches to multi-level governance and their application to policy-making in domestic, regional and global contexts.
Keywords: Decentralization in government; International relations; Intergovernmental cooperation; Regionalism (International organization)